Midface advancement in an adult patient with Crouzon syndrome: Modified LeFort III + LeFort I osteotomy accompanied by genioplasty and nasal dorsum augmentation - Milad Etemadi Sh; Golnaz Tajmiri (Wolters Kluwer Medknow Publications, 2022)
Crouzon syndrome is an autosomal dominant trait, leading to midface deficiency, undeveloped orbits, short nasal dorsum, and exophthalmos as the typical clinical features. Early correction of craniofacial problems can improve patients' quality of life, but many of these patients with Crouzon syndrome are seeking treatment in older ages when they are missed for multidisciplinary management and distraction technique in proper timing. Modified LeFort III osteotomy is one of the treatment options that can be used for proper resolution in adult patients. The present case report study aims to describe a patient with midface deficiency due to the Crouzon syndrome who has undergone a combination of modified LeFort III osteotomy with the periocular approach and LeFort I osteotomy, nasal dorsum augmentation accompanied by genioplasty, wholly as a single surgical procedure which has been shown that can result in highly satisfactory outcomes for both patient and surgeon.